2019
DOI: 10.1029/2019sw002250
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and Impact of the New York Railroad Superstorm of May 1921

Abstract: Analysis is made of low-latitude ground-based magnetometer data recording the magnetic superstorm of May 1921. By inference, the storm was driven by a series of interplanetary coronal mass ejections, one of which produced a maximum pressure on the magnetopause of~64.5 nPa, sufficient to compress the subsolar magnetopause radius to~5.3 Earth radii. Over the course of the storm, low-latitude geomagnetic disturbance exhibited extreme local time (longitude) asymmetry that can be attributed to substorm disturbance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 86 publications
(92 reference statements)
7
68
0
4
Order By: Relevance
“…Dietrich, 2013; Siscoe et al, 2006), whereas the maximal amplitude of horizontal force at Bombay was reported 1760 nT (Tsurutani et al, 2003). This hourly value is comparable to that of the May 1921 storm (see Love et al, 2019b). This comparison tells us that the Carrington event was not likely unique but one of the most extreme events.…”
Section: Space Weathermentioning
confidence: 71%
See 2 more Smart Citations
“…Dietrich, 2013; Siscoe et al, 2006), whereas the maximal amplitude of horizontal force at Bombay was reported 1760 nT (Tsurutani et al, 2003). This hourly value is comparable to that of the May 1921 storm (see Love et al, 2019b). This comparison tells us that the Carrington event was not likely unique but one of the most extreme events.…”
Section: Space Weathermentioning
confidence: 71%
“…These reports make it possible to estimate that the equatorward boundary of the auroral oval in the Eastern Hemisphere extended at least beyond the overhead positions of the Russian stations (≈37°M LAT), even during the recovery phase of the Carrington storms, after the extreme negative excursion recorded at Bombay. The conservative estimate of the equatorward boundary of auroral oval in the (Rich & Denig, 1992), S+06 (Siscoe et al, 2006), H+18a (Hayakawa, Ebihara, Willis, et al, 2018), H+18b (Hayakawa, Ebihara, Hand, et al, 2018), H+19a (Hayakawa, Ebihara, et al, 2019), L+19a (Love et al, 2019a), and L+19b (Love et al, 2019b) Note. The equatorward boundary of the auroral oval for the Hydro-Quebec Event is based on auroral particle precipitation and the auroral electric field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By any measure the storm was large: The magnetic index Kp reached 9+, the top of its scale, and the Dst value of −589 nT was the largest since the Dst index started in 1957. (Estimated Dst values of −850 to −1,760 nT for the 1859 Carrington storm and estimated Dst value of −907 nT for the May 1921 storm place these events as the largest in modern times; Siscoe et al, ; Tsurutani et al, ; Hayakawa et al, ; Love et al, .) However, the index numbers do not tell the whole story.…”
Section: Introductionmentioning
confidence: 99%
“…LOVE MAGNETIC SUPERSTORM STATISTICS 5 of 22 10.1029/2019SW002255 (Bezdek & Solomon, 1983;Mugele & Evans, 1951). We note that Vasyliūnas's upper limit on −Dst m is far higher than that which occurred for the March 1989 storm, far higher than that realized for the storm of May 1921 −Dst m = 907 nT (Love et al, 2019b), and far higher than for the Carrington event of 1859, approximately 850 nT (Siscoe et al, 2006) to 1,050 nT .…”
Section: Theoretical Statistical Modelsmentioning
confidence: 80%